PENGEMBANGAN PERANGKAT PEMBELAJARAN KOOPERATIF TIPE NHT BERBASIS LINGKUNGAN PADA MATERI POKOK SISTEM KOLOID - Syahruddin Syahruddin (Chemistry Education Review (CER), 2017)
The purpose of this study was to explain/describe the process of software development NHT type cooperative learning environment based on the subject matter of colloidal systems and to acquire the NHT type cooperative learning environment based on the subject matter of colloidal systems valid, practical and effective. Development of the learning device colloid chemistry system at SMK Negeri 6 Takalar based on the key steps in the development of 4-D model study were divided into four stages, namely: pendefenisian (define), the design (design), development (develop), and dissemination (disseminate). Developed learning tools that RPP, BS, LKS and THB validated by two experts with the results of the assessment were valid category. From the analysis of the feasibility study is in the high category with an average value of 4.09 and meet practical criteria. Student activities, student responses, and the ability to manage learning teacher at the high category and the level of success in field trials showed that mastery learning TKJ XI grade students of SMK Negeri 6 Takalar is 83.33% met the criteria of effectiveness. On analyzing the response of teachers to the learning device obtained a percentage of 81.99% which means the positive response of teachers are at very high category. Based on the criteria used to assess learning device that generated the validity, effectiveness and practicality, then the learning device developed meets the criteria for a valid, practical, and effective.